INFLUENCE OF LEADERSHIP STYLES TOWARDS ORGANIZATIONAL COMMITMENT IN AMOGHA MAJU SDN BHD, KUCHING, SARAWAK. - SUMAN, A/L MAHINDREEN (Universiti Malaysia Sarawak(UNIMAS), 2019)
This research endeavours to explore Influence of leadership styles towards organizational commitment in influencing employee and employers outcomes in the context of organisational commitment. Based on this theory, two leadership styles practices, namely, Transformational Leadership and Transactional Leadership, have been used to examine employees’ and employer’s reaction towards commitment in the organization chosen which is Amogha Maju Sdn Bhd, Kuching, Sarawak. Data were acquired from employees in administrative level through an interview questions. Thus, researcher acknowledge the employees were Influenced by Transactional and Transformational Leadership Styles.